A Case of Lacrimo-Auriculo-Dento-Digital Syndrome with Multiple Congenitally Missing Teeth - Lumbini Pathivada; Munagala Karthik Krishna; Mandeep Rallan (Case Reports in Dentistry)
Lacrimo-auriculo-dento-digital (LADD) syndrome is an extremely rare disorder which may occur sporadically or inheritably as an autosomal dominant condition. It is characterized by defects in the lacrimal apparatus, ear problems, and dental and digital abnormalities. However, specific symptoms vary greatly among the cases with a high degree of overlap with other similar genetic disorders. Here, we describe a 7-year-old boy with LADD syndrome, clinical and radiological findings, dental treatment undertaken, and its differential diagnosis.